ASSISTANCE FOR THE USE OF USED BRICKS IN FISH PONDS - Milhatun Nisa; Mar’atus Sholikhah (khidmatan, 2022)
Dasekan hamlet is known as the center of the cottage industry for brickmaking. Almost all residents become brickmakers. However, this business gradually gets sluggish, and the price is lower. The type of Research used in this study uses a qualitative case study. The method used is Participatory Action Research (PAR). The PAR method has three key variables: Participatory, Action (action), and Research (Research). The results of the initial observations indicate the potential economic value of the excavated pits for raw bricks that have yet to be utilized. During the outreach activities, the community learned how to use ex-brick excavation land in fish ponds. The follow-up to this community service activity is to carry out continuous monitoring and evaluation with STAI Lecturer Syubbanul Wathon. To facilitate coordination, a brickmaking community in Dasekan hamlet is formed so that this socialization activity has valuable benefits that the community can feel.